A new methodology for the estimation of wheel–rail contact forces at a high-frequency range. (November 2018) - Bagheri, Vahid R; Younesian, Davood; Tehrani, Parisa H
Online measurement of wheel–rail contact forces is nowadays in demand for evaluating safety and manoeuvring the condition in real time and in real operation. In this study, the wheel–rail contact forces are estimated using a novel indirect identification method based on the measured radial strain on the wheel web. Further, the strain response of the rolling wheel is derived using an analytical solution of the disk under a rotating load, and a scheme was prepared for the identification of the rolling wheel parameters and its corresponding characteristic matrix. An appropriate angular strain configuration is employed to eliminate the effect of wheel rotation. The Tikhonov regularization technique is employed to solve the ill-posed least square problem and to attenuate the effect of noisy measurement and numerical uncertainty during the estimation of the forces. A finite element model of the rotating load is then constructed to investigate the effectiveness and accuracy of the proposed methodology. The effects of the rotating speed, loading and measurement noise on the estimated normal force are studied. It is found that neglecting the effect of the rotating speed causes a notable error particularly in the high-speed range.